Kreatifitas Guru TPQ dalam Mengatasi Kesulitan Membaca Al Quran pada Anak - Mikyal Oktarina (2021)
The ability to read and write the Qur'an is very important and urgent among Muslims, because in teaching the Qur'an, children learn letters and words that they do not understand the meaning of, let alone generally children. Children only learn to read not write it. Psychologically, the children's age is quite conducive to receiving guidance on reading and memorizing the Qur'an. Of course for every TPQ teacher to be more creative in choosing to use learning methods and media to overcome students' difficulties in reading the Qur'an. Creative teachers are teachers who are able to create a fun learning atmosphere, easy to understand, able to optimize existing learning media, be open to new experiences, have the desire to find and research, think flexibly and passionately, are actively dedicated, respond to questions or have a habit of giving answers. More using the right method in teaching reading the Qur'an by looking at the factors that influence it, especially for children who are less motivated or lack enthusiasm, concentration and others. After increasing creativity by using media tricks and cool methods, children feel happy and can easily understand the material presented and there is an interest in being more active in the process of learning to read the Qur'an.